The Nature of Contract in E-Money Gopay Top-Up Transactions - Syam, Muhammad Agus; Rosidi; Adib, Noval (The International Journal of Accounting and Business Society, 2024)
Purpose — This paper attempts to explore the nature of the contract of Gopay balance top-up transactions through the accounting treatment applied by the Gopay e-money issuer and to find out the legal status of the discount and cashback provided by the Gopay e-money issuer. Design/methodology/approach — To know the law of a case, we need to look at the reality of that case. Through in-depth interviews with expert informants and exploring existing regulations, this paper finds conical realities in the contracts used in Gopay balance top-up transactions. Findings — The results of the search that has been carried out on the realities in the field and related regulations show that the Gopay balance top-up transaction uses the Qardh contract. So discounts and cashback are benefits provided by Gopay to Gopay users. Practical implications — Gopay e-money publishers should pay attention to the application of giving discounts and cashback to their users to avoid things that are prohibited by Islamic law. In addition, Gopay's business process must also ensure that the contract used is by Gopay's goals. Originality/value — This paper dissects Gopay balance top-up transaction activities from the accounting recognition point of view while also paying attention to other aspects closely related to the top-up transaction activity. This paper also presents novelty through data analysis techniques that support contemporary muamalat problems. Hopefully, this paper can add insight to the public, especially Gopay e-money users, regarding the Gopay e-money process business. Keywords — Accounting treatment, nature of the contract, top-up transactions, discounts, cashback. Paper type — Case study